The challenges of being imperfect: how do judges and prosecutors deal with sentencing disparity - Plesničar, Mojca M. (Frontiers in Sociology, 2024)
Legal decision-making aspires to be objective, a principle regarded as foundational to justice, public trust, and the legitimacy of legal outcomes. However, this ideal is often challenged by the reality of human judgment, which is influenced by subjective factors such as emotions, biases, and varying cognitive strategies. This paper investigates the psychological challenges faced by legal professionals in the context of sentencing, drawing on data from studies involving judges and prosecutors in Slovenia. Through workshops, interviews, and focus groups, the research highlights substantial inconsistencies in sentencing practices, even for similar offences. These disparities reveal the limits of objectivity within the judicial process, prompting legal professionals to reflect on the systemic and individual factors driving variability. The analysis focuses on how judges and prosecutors react to these discrepancies, examining a range of emotional and psychological responses—including the rationalization of decisions, the pursuit of consistency through personal “sentencing codes,” and reliance on collegial input to cope with the absence of formal guidelines. The analysis draws on concepts from cognitive dissonance theory, deliberate ignorance, emotional labour, and personality types to explore how professionals reconcile the ideal of objectivity with the imperfections of human judgment. It highlights the profound emotional toll that discrepancies in sentencing can take on decision-makers and how these emotional reactions influence their professional identity and approach to justice. By contextualising these findings within the sociology of emotions, this paper emphasises how the emotional realities of legal professionals shape their responses to perceived failures and impact their capacity to deliver justice. Ultimately, this study aims to foster a deeper understanding of the human aspects of judicial decision-making, underscoring the need for systemic reforms to mitigate disparities, provide support, and promote consistency in sentencing practices.